Perancangan Blanking Compound Dies pada Mesin Press Sinao Kapasitas 250 kN untuk Proses Pembuatan Ring M20 - Erwanto Erwanto; Taufiq Hidayat; Nidia Lestari; Joko Waluyo (Universitas Muhammadiyah Yogyakarta, 2021)
In this design, the product we want to make is a die for the M 20 ring because the die we designed is helpful for student learning (practicum) at the Mechanical Technology Laboratory. The ring manufacturing process is carried out using one blanking compound dies. The blanking and piercing processes are carried out in one operation, thus saving time and money. This dies planning includes the process of designing dimensions and other supporting tools using the SolidWorks 2017 application. This design aims to produce blanking compound dies designs on press machines for the M20 ring manufacturing process with little or no defects and estimate the cost of making blanking compound dies. The method of analysis using Solidworks 2017 software includes displacement, von misses stress, safety factor. The results obtained from the 2017 SolidWorks analysis are to estimate the wear life of the punch and die to anticipate product failures. The material used in this ring is SAPH440 as defined in JIS 3113, starting from 2 mm to 14 mm. At the same time, the one we use for the M20 ring has a thickness of 2 mm. Based on the dies design calculations and data analysis that has been carried out, it is concluded that the use of blanking compound dies can reduce product defects due to dimensional accuracy in the dies and accelerate the production process of ring making.